2017
DOI: 10.1016/j.envint.2016.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Associations between long-term exposure to PM2.5 component species and blood DNA methylation age in the elderly: The VA normative aging study

Abstract: Background Long-term PM2.5 exposure and aging have been implicated in multiple shared diseases; studying their relationship is a promising strategy to further understand the adverse impact of PM2.5 on human health. Objective We assessed the relationship of major PM2.5 component species (ammonium, elemental carbon, organic carbon, nitrate, and sulfate) with Horvath and Hannum DNA methylation (DNAm) age, two DNA methylation-based predictors of chronological age. Methods This analysis included 552 participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 69 publications
5
62
0
Order By: Relevance
“…Further, each method involves almost entirely non-overlapping CpG sites. Although both methods perform similarly in their prediction of mortality (14,36), previous studies have also reported differences in their associations between other traits of interest, for example exposure to environmental particulate matter (37), with neural integrity in post-traumatic stress disorder (36), and with longevity (38). These studies, together with the current findings, therefore suggest that the two DNAm age biomarkers of biological ageing may reflect subtly different aspects of the ageing process.…”
Section: Discussionsupporting
confidence: 55%
“…Further, each method involves almost entirely non-overlapping CpG sites. Although both methods perform similarly in their prediction of mortality (14,36), previous studies have also reported differences in their associations between other traits of interest, for example exposure to environmental particulate matter (37), with neural integrity in post-traumatic stress disorder (36), and with longevity (38). These studies, together with the current findings, therefore suggest that the two DNAm age biomarkers of biological ageing may reflect subtly different aspects of the ageing process.…”
Section: Discussionsupporting
confidence: 55%
“…The number of studies examining relationships of ambient PM2.5 with DNAm-age are limited, but our results are consistent with what they report 8, 10, 52 . Here, we observed comparable, significant positive associations of PM2.5, sulfate, and ammonium with DNAm-age.…”
Section: Discussionsupporting
confidence: 92%
“…We began with a total of 552 participants with 940 observations between the years 2000 and 2011. This was the study sample that was used in reporting the significant associations between PM2.5 component species and DNAm-age in our previous publication 10 . Of these 552 participants, 249 (45%) had one visit, 218 (40%) had two visits, and 85 (15%) had three or more visits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation age is a novel epigenome-wide DNA methylation-based measure of individual biological aging predicting the chronological age [58] as well as capturing the interpersonal differences in the risk of many functional alterations, diseases and mortality [59]. In adults, increased PM 2.5 exposure has been linked to accelerated DNA methylation age [6062], which provides an improved understanding of the role of PM 2.5 as a contributor to accelerated aging and aging-related diseases [6367], such as cardiopulmonary disease, cognitive decline. Other perturbation-related DNA methylation age modification are also documented.…”
Section: Epigenetic Toxicitymentioning
confidence: 99%